Inositol-Requiring Enzyme 1 pathway and autophagy drive sequential response of endothelial cells to febrile range hyperthermia - Julie Vorbe; Florence Massey; Corinne Rocher; Océane Morales; Nihal Brikci; Marie Le Borgne; Caligiuri Giuseppina; Antonino Nicoletti; Grégory Franck; Stéphane Illiano (PLoS ONE, 2025)
Context Fever is an evolutionarily conserved and adaptive response during infections. However, prolonged fever has numerous systemic metabolic and functional side effects. In the heart, prolonged fever associated with infection is linked to fatal adverse effects, particularly involving impaired coronary circulation. Yet, the direct relationship between elevated temperature and coronary microcirculation dysfunction, remains to be fully demonstrated. In this study, we aimed to explore the specific responses of human coronary artery endothelial cells (HCAECs) to fever-range hyperthermia. Method HCAECs were cultured at either 37°C or 40°C for up to 24 hours. Transcriptomic and proteomic profiles were obtained through microarray and mass spectrometry after 6, 12, and 24 hours of exposure. Key signaling pathways, upstream regulators, and candidate mechanisms were identified and validated at the mRNA and protein levels using mechanistic approaches. Results Prolonged hyperthermia compromised HCAEC function, evidenced by cell detachment, loss of junctions, and increased permeability. HCAECs rapidly activated the unfolded protein response (UPR), including IRE1α activation and XBP1 splicing. Additionally, autophagic flux was significantly elevated, participating in the degradation of junction proteins. Pharmacological inhibition of IRE1α reduced the autophagic burden, protected against cell detachment, and preserved junction integrity over time. Conclusion Our findings reveal that in response to fever-range hyperthermia, the IRE1α-autophagy axis regulates the survival and function of coronary endothelial cells. This mechanism could play a key role in modulating endothelial responses during infection and contribute to the pathological outcomes of fever. Furthermore, it may be relevant in local inflammatory conditions with elevated temperatures.